Governance and Power Dynamics in Eco-Tourism: Assessing the Co-Management Model in Nigeria's Cross River National Park - Maxwell-Borjor Achuk Eba (Universitas Negeri Makassar, 2025)
Eco-tourism in protected areas is increasingly promoted as a model for conservation and community development in Nigeria. However, its success is contingent not on the presence of biodiversity alone, but on the governance structures that manage access, benefits, and trade-offs. This research critically examines the co-management framework of Cross River National Park (CRNP), one of Nigeria's most biodiverse and internationally significant protected areas. It investigates the complex interplay between the state (National Park Service), international conservation NGOs, private tourism operators, and the numerous forest-dependent communities residing in and around the park. Using a qualitative political ecology approach, the study analyzes formal agreements, policy documents, and, crucially, the lived experiences and perceptions of local communities. It seeks to uncover whether the current co-management model facilitates genuine power-sharing and equitable benefit distribution or merely perpetuates existing hierarchies under a new,